Post-Quantum enhanced Ascon for secure vehicular IoT data integrity - Bhuvaneshwari A. J; Kaythry P.; Kishore R.; MuthuHarish R (Scientific Reports)
Abstract Secure vehicular communication is important in sustaining secure and effective transportation infrastructures. Advances in the Vehicular Internet of Things (VIoT) technology enable communication among vehicles as well as roadside facilities, offering effective traffic flow and security control. However, the vehicular networks are exposed to increased risks from cyberattacks, particularly from incoming quantum computers with the ability to interpret out-of-date conventional codes. This paper proposes a security solution based on post-quantum cryptography (PQC), which enhances Ascon encryption by adding quantum-proof key exchange. This method ensures secure authentication and protects against replay, sybil, collision, phishing, and man-in-the-middle attacks. A 32-bit Ascon hash coupled with SHA-512 provides data integrity. Investigations on resource-constrained vehicular environments confirm that the new scheme provides better performance, producing 128–512-bit keys in microseconds, much quicker than Kyber and Falcon. It also outperforms Ascon in hash rendering speed, completing a 256 × 256 grayscale image in 0.0782s, compared to 0.822s for standard Ascon, thereby emphasizing its ability to provide secure, immediate communication between vehicles in scenarios sensitive to quantum technologies. These observations show that the suggested approach is strongly secure and computationally efficient, and hence it is suitable for protecting future connected and autonomous vehicles from cyberattacks in the quantum era.